Pengaruh Product knowledge Karyawan dan Kualitas Pelayanan Islami Terhadap Kepuasan Nasabah di BTN KCS Surabaya - Nurarista, Erina Ayu; Indrarini, rachma (Jurnal Ekonomika dan Bisnis Islam, 2022)
The development of the Islamic economy has increaset the competition of Islamic banking industry. Thus, Islamic bank has to improve its customer satisfaction. Customer satisfaction is affected by product knowledge and service quality in accordance to Islamic law. This is also the focus for BTN KCS Surabaya as one of the developing Islamic Business Units. This study aimet to determine the effect of product knowledge and Islamic service quality on customer satisfaction at BTN KCS Surabaya. The data was obtained by questioner distribution to BTN KCS Surabaya customers. This study used multiple regression analysis. The results show product knowledge has no effect on customer satisfaction, and Islamic service quality affects customer satisfaction. Meanwhile, simultaneously product knowledge and Islamic service quality affect customer satisfaction at BTN KCS Surabaya.